2019
DOI: 10.1186/s12970-019-0314-7
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Status and perceptions of energy and macronutrient intake in a Group of Collegiate Female Lacrosse Athletes

Abstract: Background The purpose of this study was to compare nutritional intakes against recommended values as well as between the perceived intake and needs of female lacrosse players. Methods Twenty female NCAA Division II lacrosse players (20.0 ± 1.7 yrs., 169.7 ± 6.4 cm; 69.9 ± 10.7 kg; 27.5 ± 3.3% fat) completed a four-day monitoring period during in-season. Athletes were outfitted with an activity monitor over four consecutive days and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
94
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(100 citation statements)
references
References 29 publications
5
94
1
Order By: Relevance
“…Low energy availability values are one of many metrics that may indicate dietary insufficiencies. The athletes in the current study had a daily mean energy intake of 30 kcals/kg/day, which is below the recommended energy intake of 40–60 kcals/kg for women team sport athletes [ 7 , 40 ] and likely contributed to the high prevalence of LEA observed. Similar findings have been reported in the Under−21 United States Women’s National Soccer team, with an average daily energy intake of 34 kcals/kg/day reported [ 8 ].…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Low energy availability values are one of many metrics that may indicate dietary insufficiencies. The athletes in the current study had a daily mean energy intake of 30 kcals/kg/day, which is below the recommended energy intake of 40–60 kcals/kg for women team sport athletes [ 7 , 40 ] and likely contributed to the high prevalence of LEA observed. Similar findings have been reported in the Under−21 United States Women’s National Soccer team, with an average daily energy intake of 34 kcals/kg/day reported [ 8 ].…”
Section: Discussionmentioning
confidence: 65%
“…In the current study, suboptimal energy and macronutrient intakes were more common in athletes with LEA ( Table 2 ). The inability of collegiate athletes to meet nutritional recommendations for their respective sport is not uncommon, as it has been previously reported in both men and women athletes participating in football [ 42 ], lacrosse [ 7 ], swimming [ 6 ], basketball [ 2 ], gymnastics [ 2 ], and volleyball [ 33 ]. While nutritional recommendations have been established for women soccer athletes, the results of the current study demonstrate a continued need for sport nutrition education interventions to be part of regular team activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Future studies should further explore these barriers. Other studies have reported discrepancies between athletes perceived and actual intake, 28,29 which may in part explain the inconsistency between knowledge and behavior. Sports dietitians should educate athletes to help them reduce the discrepancy between perceived and actual intake.…”
Section: Discussionmentioning
confidence: 97%
“…When athletes do not follow these recommendations, their performance may be affected. Several crosssectional studies on athletes' dietary intake found that most of them did not meet their energy requirements during training and competition (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%